Peningkatan Pengetahuan tentang Anemia melalui Penyuluhan dan Pemberian Tablet Tambah Darah - Bachtiar Safrudin; Rinda Kurniawati; Mahathir Muhammad; Dhea Ananda Putri; Choriah Geby Anggraini; Fierdina Amalia; Nur Sausan Fauziyyah; Tiara Adinda Aulia; Ulfa Dwi Asrianti; Gatra Zakky Sabbily; Shalsa Amirah Fitri; Riki Aldi Saputra (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service activity aimed to increase adolescent girls’ knowledge about anemia prevention through education and iron tablet supplementation at MTs. Antasari, Samarinda City. The activity was conducted on Friday, November 7, 2025, involving 89 students from grades VII, VIII, and IX. The implementation included a pre-test, interactive counseling using PowerPoint and educational leaflets, a discussion session, iron tablet distribution, and a post-test for evaluation. The results showed a significant improvement in participants’ knowledge, with correct answers increasing from 61.7% in the pre-test to 94.27% in the post-test. These findings indicate that health education and direct practice of taking iron tablets effectively enhanced students’ understanding of the causes, symptoms, and prevention of anemia. This activity proved effective in fostering adolescent girls’ awareness of the importance of maintaining blood health through balanced nutrition and regular iron tablet consumption.